2020
DOI: 10.1371/journal.pone.0243237
|View full text |Cite
|
Sign up to set email alerts
|

The gamma response to colour hue in humans: Evidence from MEG

Abstract: It has recently been demonstrated through invasive electrophysiology that visual stimulation with extended patches of uniform colour generates pronounced gamma oscillations in the visual cortex of both macaques and humans. In this study we sought to discover if this oscillatory response to colour can be measured non-invasively in humans using magnetoencephalography. We were able to demonstrate increased gamma (40–70 Hz) power in response to full-screen stimulation with four different colour hues and found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
(87 reference statements)
4
5
0
Order By: Relevance
“…blue) (18). We recently replicated this NBG color tuning via invasive recordings in human visual cortex (2), with similar findings subsequently shown via noninvasive measurements (35). Similar to orientation, this color tuning of NBG is consistent with prior neuroimaging reports of an end-spectral bias in population responses within human early visual cortex, particularly V1 (30).…”
Section: Color Tuning Of Nbgsupporting
confidence: 82%
See 1 more Smart Citation
“…blue) (18). We recently replicated this NBG color tuning via invasive recordings in human visual cortex (2), with similar findings subsequently shown via noninvasive measurements (35). Similar to orientation, this color tuning of NBG is consistent with prior neuroimaging reports of an end-spectral bias in population responses within human early visual cortex, particularly V1 (30).…”
Section: Color Tuning Of Nbgsupporting
confidence: 82%
“…red / orange) (18). Recently, we reported that this color tuning of NBG can also be observed in human visual cortex (2), which was later replicated with non-invasive measurements (35). It is therefore of interest to understand how these biases in orientation and color interact to modulate population responses, in particular NBG activity.…”
Section: Nbg Displays Cardinal Orientation Selectivitymentioning
confidence: 67%
“…Oscillatory neuronal responses to full-screen colored stimuli have also been reported in MEG recordings from 20 participants (Perry et al, 2020). When full-screen red, green, purple, and blue colors were shown after a gray background or in alteration, red stimuli induced the strongest power in several oscillatory bands above 30 Hz.…”
Section: Gamma Responses To Colored Stimulimentioning
confidence: 70%
“…Large homogenous patches of color have also been shown to induce strong gamma oscillations, both in the early visual cortex of macaques (Brunet et al, 2015;Peter et al, 2019;Rols et al, 2001;Shirhatti and Ray, 2018) and humans (Bartoli et al, 2019;Li et al, 2021;Perry et al, 2020). Interestingly, red stimuli have been reported to induce especially strong gamma-band responses in several of these reports (Bartoli et al, 2019;Perry et al, 2020;Rols et al, 2001;Shirhatti and Ray, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation